Comparative Analysis of the Vertical Risk of Transmission of Some Blood-Borne Infections in the Republic of Guinea - T.A.L. Balde; S. Boumbaly; E. N. Serikova; D. E. Valutite; A. N. Shchemelev; Yu. V. Ostankova; E. B. Zueva; A. V. Semenov (Проблемы особо опасных инфекций, 2021)
The aim of our work was to compare the HBV, HCV and HIV vertical transmission risk in the Republic of Guinea.Materials and methods. The material for the study was 305 blood plasma samples from pregnant women living in Conakry, Republic of Guinea. The samples were examined for the presence of serological (HBsAg, antibodies antiHBs IgG, anti-HBcore IgG, anti-HCV IgG, Ag/Ab-HIV) and molecular (HBV DNA, HCV RNA, HIV RNA) markers.Results and discussion. When assessing the overall prevalence of serological markers among patients, the incidence of HBV markers was 76.06 %. Antibodies to HCV were detected only in 1 case, which amounted to 0.32 %. HIV markers were detected in 3 cases, which amounted to 0.98 %. The prevalence of HBsAg in the group under examination significantly differed between the groups of pregnant women aged 13–19 years (17.33 %) and 20–24 years (12.12 %), p<0.0001, RR=5.107 with 95 % CI: 2.458–10.612. When assessing the overall prevalence of molecular-biological markers among patients, we did not detect HIV RNA, in one patient, HCV RNA was determined, which was 0.32 %, while the incidence of HBV DNA was 20 %. Among HBsAg-positive individuals, HBV DNA was detected in 86.11 %, which was 10.16 % of the total group. Among the HBsAg-negative individuals, HBV DNA was detected in 11.15 % (9.84 % of the total group). It should be noted that in nine cases, HBV DNA was detected without any serological markers, which amounted to 14.75 % (2.95 % of the total group). Assessment of the blood-borne infections prevalence in pregnant women is significant for the subsequent identification of pathogen transmission routes in order to control and/or prevent the spread of infection.